Trophectoderm growth and bilateral symmetry of the blastocyst in the mouse. - Gardner, R; Davies, T (2002)
BACKGROUND: The present study was undertaken to ascertain whether the polarized flow of cells from polar to mural trophectoderm is related to the axis of bilateral symmetry of the blastocyst in the mouse, and whether trophectoderm cells can initiate new cycles once they have left the polar region. METHODS AND RESULTS: Two different approaches were used to investigate the relationship of polar to mural flow of trophectoderm cells to the bilateral axis. One was to mark peripheral polar trophectoderm cells at one or both ends of the bilateral axis in early blastocysts and examine the distribution of their clonal descendants after further growth in culture. The other was to mark the two ends of the bilateral axis with small oil drops in the zona pellucida in blastocysts whose polar trophectoderm was then labelled globally with fluorescent latex microspheres before culture. In both cases, marking of additional blastocysts orthogonal to the bilateral axis was also done. The results show that the direction of polar to mural flow of cells is not random, and that the most distal mural trophectoderm cell could yield up to eight descendants during 45 h of culture. CONCLUSION: The findings are consistent with the polar to mural flow of trophectoderm cells being aligned with the bilateral axis. Moreover, trophectoderm cells can embark on new cycles even when remote from the inner cell mass.